Advantage how American innovation can overcome the Asian challenge - Segal, Adam 1968- (New York W. W. Norton, 2011)
The emergence of India and China as economic powers has shifted the global landscape and called into question the ability of the United States to compete and maintain its technological lead. Advantage sorts out the challenges the United States faces and focuses on what drives innovation, what constrains it, and what advantages we have to leverage. Recasting the stakes of the debate, Adam Segal, an expert on technology and foreign policy, makes the compelling case for the crucial role of the "software" of innovation. By strengthening its politics, social relations, and institutions that move ideas from the lab to the marketplace, the United States can play to its greatest economic strengths and preserve its position as a global power. With up-to-the-minute economic and political data, this is a resounding call to tie innovation to larger social goals in an age of global science and technology.--From publisher description.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Technological innovations -- Economic aspects -- United States; Technological innovations -- Economic aspects -- Asia; Diffusion of innovations -- United States; Diffusion of innovations -- Asia; Entrepreneurship -- United States; Entrepreneurship -- Asia; United States -- Economic policy -- 21st century; Asia -- Economic policy